Retracted: Hepatoprotective Effects of Fractions of Adansonia Digitata Leaves on Carbon Tetrachloride (CCL4)- Induced Toxicity in Wistar Rats - Ejeh, Yakubu Ojochenemi; John, Umaru Isaac; Agyo, David Ata; Shenia, Zephaniah Hannaniah; Sunday, Gabriel; Tsuvini, Jonah; Gideon, David; Tsojon, Tsojon Zechariah; David, Bando Christopher (Asian Journal of Science, Technology, Engineering, and Art, 2024)
Phytochemicals, naturally occurring compounds in plants, offer health benefits to humans. This study aimed to determine the effects of fractions of ethanol extract of Adansonia digitata leaves on carbon tetrachloride (CCl4)-induced toxicity in wistar rats. The extraction was done using absolute ethanol, followed by fractionation with different solvent combination via column chromatography. Elution of extract was done with solvent system by gradually increasing polarity beginning from n-hexane, chloroform, ethyl acetate, methanol, ethanol and finally water. In total, 22 fractions were collected in 200 mL beaker each. The fractions were subjected to total antioxidant analysis using 1, 1-diphenyl-2-picryhydrazyl (DPPH) assay. Total phenolics and total flavonoids content were analyzed by Folin-Ciocalteu. GC-MS, FTIR and HPLC analysis were also carried out. Thirty-six male albino rats were distributed into six groups of six (n = 6). The negative control group received CCl4 only. The standard control group was administered 2 CCl4/kg body weight + 25mg/kg body weight silymarin followed by different doses of ethyl acetate:ethanol fraction-20 mg/kg, 40 mg/kg and 50 mg/kg for 21 days. Induction and treatment were carried out in the beginning of a new week. The animals were fasted for 24 hours, sacrificed and blood samples were collected for biochemical analysis. The administered fraction led to the statistically insignificant (p> 0.05) and statistically significant (p< 0.05) reduction in the levels of Aspartate aminotransferase (AST) and Alanine aminotransferase (ALT) respectively, the reduction in the levels of total protein (TP) and albumin (ALB) were statistically not significant (p> 0.05) in the treated rats as compared to the untreated rats. The phytochemical analysis of the extract revealed the presence of antioxidant and phenolics. From the total antioxidant capacity, fraction 6b (ethyl acetate: ethanol) was selected for GC-MS, FTIR and HPLC analysis. The GC-MS analysis of fraction 6b revealed the presence of 14 compounds from which Bis(2-ethylhexyl) phthalate had the highest percentage constituent (48.30%) while while 2-Methyl-Z,Z-3,13-octadecadienol had the lowest relative abundance of 0.14 %. Dichloroacetic acid, tridecyl este, d-Glycero-d-ido-heptose, Phthalic acid, ethyl pentyl ester, Trifluoroacetoxy hexadecane, 2-Hexene, 6-nitro-, 2-Tetradecanol, 3,5-Dimethyl-2-octanol, Cyclopropanecarboxylic acid, 7,11-Hexadecadienal, 9-Octadecenamide, Squalene and E, E-1,9,17-Docasatriene were the other compounds found in the fraction. FTIR spectral analysis of the fraction showed peaks of various functional groups. The HPLC results showed the presence of quercetin in the fraction.